PENERAPAN MODEL VISUALIZATION, AUDITORY, KINESTHETIC (VAK) DENGAN MULTIMEDIA DALAM PENINGKATAN KETERAMPILAN MENYIMAK CERITA PADA SISWA KELAS V SD - Urrohman, Syivaa (KALAM CENDEKIA PGSD KEBUMEN, 2016)
Abstract: The Application of Visualization, Auditory, and Kinesthetic (VAK) Model Using Multimedia in Improving Reading Skill of Story for the Fifth Grade Students of SD Negeri 1 Kalijirek in the Academic Year of 2015/2016. The objectives of this research are to describe the steps on the application of Visualization, Auditory, and Kinesthetic (VAK) model using multimedia in improving reading skill of story for the fifth grade students and to improve reading skill of story for the fifth grade students through the application of Visualization, Auditory, and Kinesthetic (VAK) model using multimedia. This research is a collaborative Classroom Action Research (CAR) conducted within three cycles in two meetings. Each cycle consisted of preparation, delivery, training, and display the result. Subjects of the research were fifth grade students of SD Negeri 1 Kalijirek totaling 21 students. The conclusion of this research are: (1) there are four steps on the application of VAK model using multimedia, namely preparation, delivery, training, and display the result and (2) the reading skill of story of the fifth grade students improved after the application of VAK model using multimedia.Keywords: VAK model, multimedia, reading skill of story Abstrak: Penerapan Model VAK dengan Multimedia dalam Peningkatan Keterampilan Menyimak Cerita pada Siswa Kelas V SD. Tujuan penelitian ini yaitu mendeskripsikan langkah-langkah penerapan model visualization, auditory, kinesthetic (VAK) dengan multimedia dalam peningkatan keterampilan menyimak cerita pada siswa kelas V SD; serta meningkatkan keterampilan menyimak cerita kelas V SD melalui penerapan model VAK dengan multimedia. Penelitian ini merupakan PTK kolaboratif dan dilaksanakan dalam tiga siklus yang setiap siklusnya terdiri atas tahap persiapan, penyampaian, pelatihan, dan penampilan hasil. Subjek penelitian adalah siswa kelas V sejumlah 21 siswa. Simpulan penelitian ini yaitu: (1) langkah-langkah penerapan model VAK dengan mutimedia terdiri atas empat yaitu: tahap persiapan, penyampaian, pelatihan, dan penampilan hasil; serta (2) keterampilan menyimak cerita siswa kelas V SD mengalami peningkatan setelah menerapkan model VAK dengan multimedia. Kata Kunci: VAK, multimedia, keterampilan menyimak cerita.